Effects of regional information and internal control systems on financial report quality and fraud prevention - Nisa, Afidhiena Raisyan; Zuhroh, Diana; Cahyaningsih, Diyah Sukanti (Journal of Contemporary Accounting, 2026)
This study analyses the influence of the Regional Government Information System (SIPD) and the Government Internal Control System (SPIP) on the quality of regional financial reports and their implications for fraud prevention in 38 regencies/cities in East Java. Secondary data were obtained from the Supreme Audit Agency (BPK) and the Ministry of Home Affairs for the 2021-2023 period and then analysed using Partial Least Squares (PLS). The results demonstrate that financial report quality has a positive and significant effect on fraud prevention, in line with the fraud triangle theory, which states that transparency can minimise fraud opportunities. However, a unique finding reveals that financial report quality, as a mediator, is unable to channel the positive influence of SIPD and SPIP on fraud prevention. The implication is that, despite the system being reported as operational and the report quality being deemed good, fraud still has the potential to occur. These findings underscore the importance of enhancing human resource competency in the effective implementation of internal control systems. The study results are expected to provide valuable input for local governments and regulators in their efforts to mitigate fraud risks.